2022
DOI: 10.1039/d1ra07321d
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Ag(0) nanoparticles on quaternary ammonium functionalized polyacrylonitrile fiber as a highly active catalyst for 4-nitrophenol reduction

Abstract: Ag(0) nanoparticles were immobilized on various pyridine salt, imidazole salt and quaternary ammonium functionalized polyacrylonitrile fibers (PANFs) to prepare Ag(0)-immobilized fiber catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Crown ether phase-transfer catalysts generally have higher lipophilicity than onium salt phase-transfer catalysts, and their catalytic ability is stronger than onium salts (Figure 7). Supported phase-transfer catalysts, which are insoluble in water, acids, bases, and organic solvents, can be recovered simple filtration after the reaction, can be reused, and are very suitable for continuous industrial production [63][64][65]. Support types include organic supports (polystyrene resin, chlorinated polyethylene) and inorganic supports (silica gel, alumina).Typical three-phase phase transfer catalysts include immobilized ammonium salt, immobilized polyethylene glycol, immobilized crown ether, etc.…”
Section: Crown Ether and Polyether Phase-transfer Catalystmentioning
confidence: 99%
“…Crown ether phase-transfer catalysts generally have higher lipophilicity than onium salt phase-transfer catalysts, and their catalytic ability is stronger than onium salts (Figure 7). Supported phase-transfer catalysts, which are insoluble in water, acids, bases, and organic solvents, can be recovered simple filtration after the reaction, can be reused, and are very suitable for continuous industrial production [63][64][65]. Support types include organic supports (polystyrene resin, chlorinated polyethylene) and inorganic supports (silica gel, alumina).Typical three-phase phase transfer catalysts include immobilized ammonium salt, immobilized polyethylene glycol, immobilized crown ether, etc.…”
Section: Crown Ether and Polyether Phase-transfer Catalystmentioning
confidence: 99%
“… 28 Quaternary ammonium salts can stabilize Ag 0 nanoparticles through electrostatic interactions and steric effects, and the halogen ions can stabilize the Ag 0 nanoparticles through chelation. 29 As far as we know, few studies have been conducted to prepare AgNPs by using cationic cyclodextrins as reducing and stabilizing agents. In addition, their different complexation and solubilization capabilities make them an ideal host to construct inclusion complexes with guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] However, on account of the high surface energy and uncontrollable aggregation and precipitation, the development of AgNPs has been restricted to a great extent. [41,42] One of the effective methods to address this issue is to modify AgNPs with macrocyclic aromatic skeleton to prevent the undesirable overgrowth and aggregation of AgNPs. [43][44][45][46] For example, Zhao et al reported a carboxylate pillar [6]arene-modified AgNPs-functionalized 2D hybrid material (WP6@Ag@COF) in 2019, displaying enhanced sensing capability for paraquat.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles have attracted much attention in chemistry and material communities during the past decades, [16‐23] among which silver nanoparticles (AgNPs) with unique stability, uniformity, and biocompatibility exhibited widespread applications in many research fields, including but not limited to optical sensing, [24‐27] catalytic degradation, [28‐31] biomedicine, [32‐34] electronics [35‐37] and antibacterial [38‐40] . However, on account of the high surface energy and uncontrollable aggregation and precipitation, the development of AgNPs has been restricted to a great extent [41,42] . One of the effective methods to address this issue is to modify AgNPs with macrocyclic aromatic skeleton to prevent the undesirable overgrowth and aggregation of AgNPs [43‐46] .…”
Section: Introductionmentioning
confidence: 99%